The effect of the pesticide, endosulfan, on hepatic cytochrome P-450, liver and gill ultrastructure, and selected haematological parameters of Oreochromis Mossambicus (Peters, 1852) (Pisces : Cichlidae) - Quick, Arthur Joseph Rex (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1986)
Two possible ways in which fish may acclimate to prolonged exposureÂ· to sublethal levels of endosulfan were investigated: induction of the hepatic monooxygenase system and changes in haematology. These studies also involved an examination of the ultrastructure of liver and gill tissue. Endosulfan caused none of the characteristic phenobarbital-type inductive effects on the liver of Oreochromis mossambicus. There was no increase in cytochrome P-450 levels, microsomal protein or hepatosomatic index. The reasons for the lack of induction are discussed. The effect of endosulfan on the following haematological parameters was determined: haemoglobin, erythrocyte count, microhaematocrit, mean erythrocyte volume and mean erythrocyte haemoglobin concentration. The only effect was an increase in erythrocyte count. The value of changes in haematological parameters as indicators of pollutioninduced anemia in the field is discussed. No changes in gill ultrastructure were noted although electron micrographs of liver tissue showed lesions in hepatocytes. The diagnostic value of pollution-induced pathological changes on cell ultrastructure are discussed. Recommendations are made with regard to future large scale application of pesticides on or near large water bodies
Keywords: Pesticides; Mozambique tilapia; Cichlids